Answer:
f(x) = x^4 - x^3 - 7x^2 + x + 6
Explanation:
Please, always share the instructions with every question you post. I am assuming that you are to write out the factors corresponding to the given roots, thus constructing a 4th degree polynomial, and then performng the multiplication necesssary to produce that polynomial with terms in descending order by power of x. Note that there must be 5 such terms.
f(x) = (x + 2)(x + 1)(x - 1)(x - 3)
Multiplying this out, we get:
f(x) = (x + 2)(x^2 - 1)(x - 3), or
f(x) = (x^3 - x + 2x^2 - 2)(x - 3), or:
f(x) = (x^3 + 2x^2 - x - 2)(x - 3), or:
f(x) = x^4 + 2x^3 - x^2 - 2x - 3x^3 - 6x^2 + 3x + 6
Combining like terms, we get:
f(x) = x^4 - x^3 - 7x^2 + x + 6
Note that because this is a 4th degree polynomial, the end behavior resembles that of the graph of y = x^4. As x increases, y initially decreases in Quadrant II, passes through the y-intercept (0, 6), and then increases without bound in Quadrant I.